Pós-verdade e fake news na eleição presidencial de 2018: sexualidade e pânico no contemporâneo - Barbieri, Laíssa França (2021)
The present dissertation aims at understanding contemporary phenomena – such as posttruth and fake news – and investigates the substance of some of the main fake news that were spread during the course of Brazil’s 2018 presidential campaign. The main objective is to analyze some of the fake news spread throughout Jair Bolsonaro’s presidential campaign and identify the content of some of the main messages disseminated and their effects on society. Thus, the question that supports the research problem is: What is the content of the fake news broadcast during Jair Bolsonaro's 2018 electoral campaign and what was its effect on society? To answer that question, a qualitative and bibliographic research has been carried out, supported by a vast and interdisciplinary theoretical framework. The corpus was obtained from online material, indicating the main fabricated news that circulated during the 2018 Brazilian presidential campaign. In addition, the present dissertation relies on Foucault’s studies, mostly the concept of apparatus, to conduct a situational analysis and verify the hypothesis to which individuals’ sexuality is put front and center in a discursive blend that, notably, was intended to promote moral panic within the society.